2021
DOI: 10.1103/physrevlett.126.067401
|View full text |Cite
|
Sign up to set email alerts
|

Topological One-Way Large-Area Waveguide States in Magnetic Photonic Crystals

Abstract: We have theoretically and experimentally achieved large-area one-way transport by using heterostructures consisting of a domain of an ordinary photonic crystal (PC) sandwiched between two domains of magnetic PCs. The non-magnetized domain carries two orthogonal one-way waveguide states which have amplitude uniformly distributed over a large-area. These two waveguide states support unidirectional transport even though the medium of propagation is not magnetized. We show both experimentally and numerically that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…The one-way edge states are confined at the interface between specific topological structures and possess group velocities pointing at only one direction that is determined by the direction of a magnetic field. The commonly used gyromagnetic materials are yttrium-iron-garnet (YIG) (Wang et al, 2008;Lian et al, 2012;Li et al, 2020;Ma et al, 2020;Wang et al, 2021), vanadium-doped calcium-iron-garnet (Shen et al, 2012), and gyroelectric material such as CuFe 2 O 4 (Wu et al, 2018).…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…The one-way edge states are confined at the interface between specific topological structures and possess group velocities pointing at only one direction that is determined by the direction of a magnetic field. The commonly used gyromagnetic materials are yttrium-iron-garnet (YIG) (Wang et al, 2008;Lian et al, 2012;Li et al, 2020;Ma et al, 2020;Wang et al, 2021), vanadium-doped calcium-iron-garnet (Shen et al, 2012), and gyroelectric material such as CuFe 2 O 4 (Wu et al, 2018).…”
Section: Theorymentioning
confidence: 99%
“…(B) The Faraday isolator and (C) more compact Voigt isolator (Asadchy et al, 2020). (D) Simulated electric field intensity distributions of the one-way large transport at 11.9 GHz in the heterostructures with a void defect (Wang et al, 2021). (E) Electric field profiles at the frequencies of 4.…”
Section: One-way Optical Waveguidementioning
confidence: 99%
See 2 more Smart Citations
“…Inspired from the discovery of condensed quantum Hall effect, many studies have shown that topological states show essentially single-particle behavior of electrons and one can establish an analogy relationship with photon behaviors called topological photonic state (or topological one-way edge state) [4][5][6][7]. Topological one-way edge state provides a powerful platform for novel photonic devices with nontrivial functionalities and excellent performances, such as one-way waveguide [8][9][10][11][12], topological laser [13][14][15][16][17], rainbow trapping phenomenon [18][19][20][21], dispersionless slow light [22][23][24], topological fibre [25][26][27].…”
Section: Introductionmentioning
confidence: 99%